Pelatihan dan Pengembangan Manajemen Sumber Daya Manusia Berkelanjutan - Fitrotin Nufus; Gabriella Niskha Mareta Wibisono; Elza Elza; Talitha Aurellia Andia; Dewi Nuraini (Jurnal Ilmiah Ekonomi dan Manajemen Indonesia, 2026)
Human resources (HR) are a key factor in determining an organization's success. Facing an increasingly competitive business environment, organizations are required to continuously improve the quality of their HR through ongoing training and development programs. This study aims to analyze the role of HR training and development in enhancing employee competency and performance. The research method used was a qualitative approach with a literature review, reviewing various scientific sources such as journals, books, and related articles. The study results indicate that training plays a role in improving employees' technical skills and short-term performance, while development focuses more on enhancing conceptual abilities and readiness for future responsibilities. Furthermore, the success of training and development programs is influenced by the appropriateness of the material, implementation methods, instructor competence, and systematic evaluation. Therefore, organizations need to design structured, sustainable, and needs-based training and development programs to enhance organizational competitiveness.